Huangqi Guizhi Wuwu Decoction Improves Inflammatory Factor Levels in Chemotherapy-induced Peripheral Neuropathy by Regulating the Arachidonic Acid Metabolic Pathway - Wang, Shanshan; Du, Xiaohui; Yan, Guangli; Yang, Le; Sun, Hui; Zhang, Xiwu; Kong, Ling; Han, Ying; Han, Di; Tang, Songyuan; Wang, Xijun (Current Pharmaceutical Design, 2024)
BackgroundChemotherapy-induced Peripheral Neuropathy (CIPN) is a common complication that arises from the use of anticancer drugs. Huangqi Guizhi Wuwu Decoction (HGWWD) is an effective classic prescription for treating CIPN; however, the mechanism of the activity is not entirely understood.ObjectiveThis study aimed to investigate the remedial effects and mechanisms of HGWWD on CIPN.MethodsChanges in behavioral, biochemical, histopathological, and biomarker indices were used to evaluate the efficacy of HGWWD treatment. Ultra-high-performance liquid chromatography/mass spectrometry combined with the pattern recognition method was used to screen biomarkers and metabolic pathways related to CIPN. The results of pathway analyses were verified by protein blotting experiments.ResultsA total of 29 potential biomarkers were identified and 13 metabolic pathways were found to be involved in CIPN. In addition HGWWD reversed the levels of 19 biomarkers. Prostaglandin H2 and 17α,21-dihydroxypregnenolone were targeted as core biomarkers.ConclusionThis study provides scientific evidence to support the finding that HGWWD mainly inhibits the inflammatory response during CIPN by regulating arachidonic acid metabolism.
Keywords: Chemotherapy-induced Peripheral Neuropathy (CIPN)